2021
DOI: 10.3389/fimmu.2021.672737
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Abacavir-Induced Remodelling of the Major Histocompatibility Complex Class I Peptide Repertoire

Abstract: Abacavir hypersensitivity syndrome can occur in individuals expressing the HLA-B*57:01 major histocompatibility complex class I allotype when utilising the drug abacavir as a part of their anti-retroviral regimen. The drug is known to bind within the HLA-B*57:01 antigen binding cleft, leading to the selection of novel self-peptide ligands, thus provoking life-threatening immune responses. However, the sub-cellular location of abacavir binding and the mechanics of altered peptide selection are not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…4 ). This implies that the activation of CD8 + T cells still occurs based on the effect of abacavir on antigen presentation, consistent with previous studies ( 21 , 22 ). However, abacavir-induced recruitment of inflammatory cells to the skin was reliant on HLA polymorphism-dependent ER stress responses in keratinocytes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4 ). This implies that the activation of CD8 + T cells still occurs based on the effect of abacavir on antigen presentation, consistent with previous studies ( 21 , 22 ). However, abacavir-induced recruitment of inflammatory cells to the skin was reliant on HLA polymorphism-dependent ER stress responses in keratinocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Since we observed an HLA polymorphism-dependent intracellular response to abacavir, we hypothesized that HLA could bind to abacavir intracellularly. Although not yet confirmed, the abacavir parent drug has been predicted to interact with HLA-B*57:01 in the ER ( 21 , 22 ). Consistent with a previous study ( 20 ), we demonstrated the binding of HLA-B*57:01 to abacavir using HeLa cells in which HLA was transiently expressed ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that HLA-B*5701 is necessary for the development of abacavir hypersensitivity syndrome (AHS) 9 . Abacavir is able to alter the self-peptide loading into HLA-B*57:01, co-occupy the groove and selectively affect the formation of HLA-B*57:01-peptide complexes thus provoking immune responses 7 , 10 12 . Cytotoxic CD8+ T cells drove systemic reactions to abacavir by drug-specific activation which could only be mediated by HLA-B*57:01 and not closely related, non-AHS associated allotypes 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%